Measurement of the radiation pollution of radon in selected locations from Saladin Governorate by using the nuclear track detector - Sabah Mahmoud Aman Allah; Saif Amer Mahdi; Yassen Hameed Mahmoud (Tikrit Journal of Pure Science, 2023)
The aim of  present paper to find the contamination  selected area in Salahdin governorate where the radon gas concentration elevated and they are :Al-Qadasaia quarter ,Hamad Shahab village (communication center in past),Al-douloyea town –Youths center, Dijala town ,samara city (in house garden) and finally in Beji city (communication tower) .In this study ,we had employed the trace detector of CR-39, the obtained results shows the radon concentration exceeds the permissible limits which issues by ICRP which is about 200 – 800 Bq/m3  while the concentration in Salah din governorate  is - which refers to the high ratio of depleted  Uranium all over the gubernator